Knowledge on intellectual property as an advantage for scientific research - Zermeño Guerrero, Jennifer; Garza Ruíz, Marisela; Rodríguez Padilla, Cristina (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Protection of intellectual property represents a key factor for the establishment of particular rights in the scientific sector, and a clear registry of the technological development of a country. Strategies for the protection of industrial and intellectual property and copyright are relevant to maintain the administration of knowledge under control, confidentiality during its development, and assurance of exclusivity in research activities. The relationship between colleagues when presenting at a conference should be of trust, however, plagiarism is one of the main worries among researchers whenever they have to communicate their work among experts. Our objective was to identify the reasons why researchers do not protect their scientific work. Through our survey, we found that there is a lack of knowledge regarding protection of intellectual property. We conclude that it is important to educate researchers on the importance of protecting their work to improve the relationship of trust that exists between colleagues and students.